PENGARUH PELUMURAN SERBUK DAUN OREGANO (ORIGANUM VULGARE) TERHADAP DAYA SIMPAN DAGING AYAM SEGAR - Boneta, Andi Adinda; Nazaruddin, Nazaruddin; amaro, moegiratul (Fakultas Teknologi Pangan dan Agroindustri, Universitas Mataram, 2023)
This research is oriented to determine the effect of the shelf life of chicken meat by coating it with oregano leaf powder (Origanum vulgare). The method implemented in the research was a Completely Randomized Design (CRD) with a single factor, namely (length of storage: 0 hours, 4 hours, 6 hours, 8 hours, 10 hours and 12 hours) with repetition 3 times. The parameters observed in this research were chemical, microbiological and organoleptic parameters. Chemical parameters include pH and water content analysis, microbiological parameters include total microa tests, while oreganoleptic parameters include appearance, aroma, texture and taste. The results of the research prove that long storage treatment with a coating of Duan oregano powder can maintain the quality of chicken meat for up to 10 hours based on a pH of pH 5.64; water content 67.24%, total microbes 5.92 Log CFU/gr; with organoleptic aroma, color and texture that the panelists can accept.